UPAYA MENINGKATKAN PERILAKU MORAL AGAMA PADA ANAK USIA 4-5 TAHUN MELALUI VALUE CLARIFICATION TECHNIQUE (VCT) MODEL CERITA DI RA BUNDA SUWARNI PEKANBARU - Silfia Andeni; Zulkifli Zulkifli; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study are as follows: 1) To determine the Religious Moral Behavior in children aged 4-5 years in RA Mother Suwarni Pekanbaru. 2) To find out how to improve religious moral behavior in children aged 4-5 years to implement Value Clarification Technique (VCT) model of RA Mother Suwarni story in Pekanbaru. 3) To know Value Clarification Technique (VCT) models can improve the story of Religious Moral Behavior in children aged 4-5 years in RA Mother Suwarni Pekanbaru. 4) an increase in religious moral behavior in children aged 4-5 years by Value Clarification Technique (VCT) model of RA Mother Suwarni story in Pekanbaru. This type of research that is in use dalamn this research is PTK. The research sample is graders B consisted of 11 children, consisting of 6 men and 5 women. Collecting data using observation and documentation. The data analysis technique used in this study is t test analysis techniques. The result showed an increased percentage of religious moral behavior in children aged 4-5 years with the implementation of VCT models RA story in Pekanbaru Suwarni Mother can be seen from the Pre cycle or before application to the second cycle. In the preliminary data obtained an average percentage of 50.3%. While the value of the first cycle to 69.4%. The next and the second cycle increased by 87.6% .with value thus able to improve the implementation of VCT religious moral behavior in children aged 4-5 years in Ra Mother Suwarni Pekanbaru religion as moral behavior in children increases every cycle.Keywords: application VCT model of story, the religious moral behavior